Silence and time: veiled energies in education - Casadei, Rita (Studi sulla Formazione/Open Journal of Education, 2019)
Arguments about the experience of silence may seem contradictory, and perhaps they are. The intention of this contribution is not to give voice to silence, but to give body, weight and importance to silence in the educational experience, in relationships, in reflection, in thinking and acting. I start from the consideration of silence as the matrix of listening and therefore the matrix of a dialogue, not dialectical, but dialogical, with oneself, with the other, with the Cosmos. As a "matrix" that in-form, silence contains idea and forms, inspiration and creativity, thought and gesture; it takes shape as a space and time that constitute an aesthetic experience, full of knowledge and understanding, meaning and sense, intelligence and sensitivity. Giving body to silence allows us to illuminate the dimension not manifested - but generative - of the relationship and of a communication that is not only transmission and emission, but also listening and receptiveness. It means giving meaning to time, not only as a pressing urging of speed, but as a “in-between” within which to let something happen: a new meaning, a new sense, the discovery of an authentic relationship and a renewed action.